Role of TWEAK in Lupus Nephritis: A bench-to-bedside review - Michaelson, Jennifer S. (2012)
There is significant unmet need in the treatment of lupus nephritis (LN) patients. In this review, we highlight the role of the TWEAK/Fn14 pathway in mediating key pathologic processes underlying LN involving both glomerular and tubular injury, and thus the potential for renal protection via blockade of this pathway. The specific pathological mechanisms of TWEAK – namely promoting inflammation, renal cell proliferation and apoptosis, vascular activation and fibrosis – are described, with supporting data from animal models and in vitro systems. Furthermore, we detail the translational relevance of these mechanisms to clinical readouts in human LN. We present the opportunity for an anti-TWEAK therapeutic as a renal protective agent to improve efficacy relative to current standard of care treatments hopefully without increased safety risk, and highlight a phase II trial with BIIB023, an anti-TWEAK neutralizing antibody, designed to assess efficacy in LN patients. Taken together, targeting the TWEAK/Fn14 axis represents a potential new therapeutic paradigm for achieving renal protection in LN patients.